PHOTOSYSTEM II INHIBITOR HERBICIDES - PART II - SILVA, ILCA P. DE F. E; JUNIOR, JOSUÉ F. DA S.; PUTTI, FERNANDO F.; LATORRE, DEBORA DE O.; SCHIMIDT, ANA P.; LUDWIG, RAFAEL (Revista Brasileira de Engenharia de Biossistemas, 2013)
The herbicide inhibitors of photosystem II (PSII) bind to the QB site located in D1 protein which is located at the thylakoid membrane of the chloroplast, causing the blocking transport of electrons from QA to QB, resulting in peroxidation of lipids. The main factors affecting the evolution of weeds resistance to herbicides have been grouped into: genetic, bio-ecological and agronomic. The weeds resistance to herbicides is defined as the ability of a plant to survive and reproduce, upon exposure to otherwise lethal dose of herbicide for a normal plant biotype. The selectivity of a herbicide is related to the ability to eliminate weeds without affecting the quality of economic interest plant.